The exiles and presence in Costa Rica of Nicaraguans, during the decades of the 30s and 40s of the 20th century - Chacón Araya, German (2020)
This article is part of the research project “El Seminario Permanente-Exilio Iberoamericano” (translated as “The Permanent Seminar-Ibero-American Exile”), and the PAPIIT Project IA 600314 of CIALC, both from UNAM (Mexico).  The Universidad Nacional (Costa Rica) is counterpart of these projects through IDELA, by expanding the scope of investigation within the Jornadas del Exilio Iberoamericano (translated as Ibero-American Exile Journeys) research project.  The present investigation has sought to venture into a sparsely studied subject: the long exile lived in Costa Rica by Nicaraguan members of the “Ejército de Liberación de Sandino y sus bases sociales” (translated as “Sandino Liberation Army and its social bases”), after the murder of its maximum leader, in the hands of the Somozas in early the 1930s.  These individuals did not renounce defeating the dictatorship and participated in clobbering the Somocista forces, until the triumph of the Sandinista Revolution; for 49 years they lived a particular exile, incorporated in the defense of Costa Rica’s Garantías Sociales (translated as Social Guarantees) and Código de Trabajo (translated as Labor Code), fighting as militiamen at the juncture that led to the civil war of 1948, where a large number offered their blood, for the homeland that welcomed them.